The queen of blood (Queens of Renthia, 1, 1, 2016)
In Renthia, everything has a spirit: the willow tree with leaves that kiss the pond, the stream that feeds the river. But the spirits of the land want to rid it of all humans. The queen is the only woman who stands between the spirits and the end of humankind, and no matter how strong or good the queen is, the threat of danger always looms. And so, Daleina is one of the young women chosen and trained as heirs to the throne. She joins forces with Ven, a disgraced champion who has nevertheless spent his exile secretly fighting against the growing number of spirit attacks. The partners embark on a quest to find the source of the spirits' restlessness, which will test their courage and trust, and force them to stand against both enemies and friends to save their land. --

The reluctant queen (Queens of Renthia, 2, 1, 2017)
Filled with political intrigue, violent magic, and malevolent spirits, the mesmerizing second book in Sarah Beth Durst's Queens of Renthia epic fantasy trilogy. Everything has a spirit: the willow tree with leaves that kiss the pond, the stream that feeds the river, the wind that exhales fresh snow ... And those spirits want to kill you. It's the first lesson that every Renthian learns. Not long ago, Daleina used her strength and skill to survive those spirits and assume the royal throne. Since then, the new queen has kept the peace and protected the humans of her land. But now for all her power, she is hiding a terrible secret: she is dying. And if she leaves the world before a new heir is ready, the spirits that inhabit her beloved realm will run wild, destroying her cities and slaughtering her people. Naelin is one such person, and she couldn't be further removed from the Queen--and she wouldn't have it any other way. Her world is her two children, her husband, and the remote village tucked deep in the forest that is her home, and that's all she needs. But when Ven, the Queens champion, passes through the village, Naelin's ambitious husband proudly tells him of his wife's ability to control spirits--magic that Naelin fervently denies -- Provided by publisher.

The queen of sorrow (Queens of Renthia, 3, 1, 2018)
Queen Dalenia believes she can bring about peace with the powerful Queen Naelin by her side, but Naelin's children are captured by spirits and things start to fall apart. Queen Daleina's dreams of bringing peace and prosperity to her forest home seemed doomed when neighboring forces invaded Aratay. Now, ruling alongside Queen Naelin, those dreams seem closer ... even in a land plagued by malevolent nature spirits who thirst for the end of human life. When Naelin's children are kidnapped by spirits, Naelin blames Queen Merecot of Semo for the kidnapping. But taking the children is merely one step in a plot to change the future of all Renthia, either by ending the threat of spirits once and for all-- or plunging the world into chaos. -- adapted from jacket.

The deepest blue: tales of Renthia (Queens of Renthia, , 1, 2019)
Life is precious and precarious on the islands of Belene. Besieged by a capricious ocean full of malicious spirits, the people of the islands seek joy where they can. Mayara, one of the island's fearless oyster divers, has found happiness in love. But on the day of her wedding to the artist Kelo, a spirit-driven storm hits the island with deadly force. To save her loved ones, Mayara reveals a dangerous secret: she has the power to control the spirits. When the storm ends, she is taken into custody by the queen's soldiers and imprisoned with other women like her. They vary in age and social status, but to many they are heroes who will aid the country or witches that will sacrifice themselves trying. No matter who they are, the women are sent to a terrifying place--an island filled with bloodthirsty nature spirits, and left without food, water, shelter, or any tools except their own instincts and magic. Whoever survives the Island of Testing will be declared heirs to the queen. But no matter if she wins or loses, Mayara knows that the life she dreamed of is gone.